Antimicrobial Resistance Pattern in Escherichia coli Isolates Obtained from a Specialized Women and Children Hospital in Shiraz, Iran: A Prevalence Study - Mahtab Hadadi; Yalda Malekzadegan; Hamid Heidari; Hadi Sedigh Ebrahim-Saraie; Mohammad Motamedifar (Shiraz University of Medical Sciences, 2016)
Abstract Background: Escherichia coli, known as a clinically significant bacteria, can cause a wide range of infections, including urinary tract infections (UTIs), blood stream infections (BSIs), and can frequently be isolated from various clinical specimens. Evaluation of antimicrobial resistant pattern is a necessary action, especially about such bacteria which are frequent and life threatening. The aim of this study was to determine the frequency and antimicrobial resistance pattern of E. coli isolates obtained from various clinical specimens. Methods: This retrospective study was performed within a seven month period from January 2015 to August 2015 at a specialized women and children hospital in Shiraz, Iran. E. coli isolates were obtained from various clinical specimens and identified using standard microbiological procedure. Antimicrobial susceptibility patterns were determined using disk diffusion method in accordance with CLSI recommendation. Results: Of the total 130 positive cultures, the majority of E. coli isolates were obtained from urine (96=73.8%) and blood (11=8.5%) specimens. Overall, gentamicin (70.8%) was the effective antibiotic for the tested E. coli isolates. E. coli isolates obtained from urine specimens showed the highest resistance rates against ampicillin (84.4%) and nalidixic acid (61.5%); while they showed the most sensitivity to gentamicin (79.2%), nitrofurantoin (70.8%) and ciprofloxacin (66.7%). Moreover, the highest antibiotic resistance rates belonged to the isolates recovered from endotracheal tube (ETT). Conclusion: The results showed that gentamicin was the most effective antibiotic against E. coli infections. However, in addition to the gentamicin, we can recommend nitrofurantoin and ciprofloxacin as the other effective agents for UTIs